Magnetic nanoparticles: an emerging technology for malignant brain tumor imaging and therapy - Wankhede, Mamta (2012)
Magnetic nanoparticles (MNPs) represent a promising nanomaterial for the targeted therapy and imaging of malignant brain tumors. Conjugation of peptides or antibodies to the surface of MNPs allows direct targeting of the tumor cell surface and potential disruption of active signaling pathways present in tumor cells. Delivery of nanoparticles to malignant brain tumors represents a formidable challenge due to the presence of the blood–brain barrier and infiltrating cancer cells in the normal brain. Newer strategies permit better delivery of MNPs systemically and by direct convection-enhanced delivery to the brain. Completion of a human clinical trial involving direct injection of MNPs into recurrent malignant brain tumors for thermotherapy has established their feasibility, safety and efficacy in patients. Future translational studies are in progress to understand the promising impact of MNPs in the treatment of malignant brain tumors.